Clinical measures of foot posture and ankle joint dorsiflexion do not differ in adults with and without plantar heel pain - Karl B. Landorf; Michelle R. Kaminski; Shannon E. Munteanu; Gerard V. Zammit; Hylton B. Menz (Scientific Reports, 2021)
Abstract Foot posture and ankle joint dorsiflexion have long been proposed to be risk factors for plantar heel pain, however body mass may be a confounder when investigating these factors. The aim of this study was to determine if clinical measures of foot posture and ankle joint dorsiflexion differ in adults with and without plantar heel pain after accounting for body mass. This was a cross-sectional observational study that compared 50 participants with plantar heel pain to 25 control participants without plantar heel pain who were matched for age, sex and body mass index. Foot posture was assessed using the Foot Posture Index and the Arch Index. Ankle joint dorsiflexion was assessed with a weightbearing lunge test with the knee extended and with the knee flexed. No significant differences (P < 0.05) were found between the groups for foot posture, whether measured with the Foot Posture Index or the Arch Index. Similarly, no significant differences were found in the weightbearing lunge test whether measured with the knee extended or with the knee flexed. Clinical measures of foot posture and ankle joint dorsiflexion do not differ in adults with and without plantar heel pain when body mass is accounted for. Therefore, clinicians should not focus exclusively on foot posture and ankle dorsiflexion and ignore the contribution of overweight or obesity.